PENGARUH PERPUTARAN MODAL KERJA, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP RETURN ON ASSET PADA PT. AGUNG PODOMORO LAND Tbk PERIODE 2014-2023 - Puteri Azahra; Diana Riyana Harjayanti (Journal of Research and Publication Innovation, 2025)
This study was conducted with the aim of testing the Effect of Working Capital Turnover, Receivables Turnover and Inventory Turnover on Return On Assets at PT. Agung Podomoro Land Tbk partially and simultaneously. This study uses a quantitative method by obtaining secondary data to determine the effect between independent variables on dependent variables and formulate hypotheses to be tested. The data population used in this study is the financial report data of PT. Agung Podomoro Land Tbk. While the sample used in this study is the financial position report and profit and loss report with a period of 10 years starting from 2014-2023. The data analysis techniques used in this study consist of Descriptive Test, Classical Assumption Test, Simple Linear Regression Analysis, Multiple Linear Regression Analysis, Hypothesis Test, Correlation Coefficient and Determination Coefficient. Data management in this study used SPSS (Statistical Product and Service SolutionI) version 27. The results of this study state that partially the Effect of Working Capital Turnover does not have a significant effect on Return On Asset with a calculated t value <t table (-1.752 <2.447) and a sig. value> 0.05 (0.130> 0.05). Then partially the Effect of Receivables Turnover has a significant effect on Return On Asset with a calculated t value> t table (6.907> 2.447) and a sig. value <0.05 (0.000 <0.05). Furthermore, partially Inventory Turnover has a significant effect on Return On Asset with a calculated t value> t table (4.782> 2.447) and a sig. value <0.05 (0.003> 0.05). Simultaneously, Working Capital Turnover, Accounts Receivable Turnover and Inventory Turnover have a significant influence on Return On Asset with Fcount>Ftable (22.460>4.76) and sig. <0.05 (0.001<0.05). The Determination Coefficient value shows that Working Capital Turnover, Accounts Receivable Turnover and Inventory Turnover explain the Return On Asset variable by 91.8% of Return On Asset, while the remaining 8.2% is influenced by other variables not examined in this study.